Association of affective state with the assimilation of daily pain expectancy and pain experience. Issue 11 (7th November 2022) - Finan, Patrick H.; Hunt, Carly A.; Mun, Chung Jung; Lerman, Sheera F.; Tennen, Howard; Smith, Michael T.; Haythornthwaite, Jennifer A.
Abstract : Supplemental Digital Content is Available in the Text. In the course of daily life with chronic temporomandibular pain, pain expectancies influence the experience of pain. When positive affect is elevated, expectancies for lower than usual pain are more likely to be associated with lower experienced pain. Abstract: Expectancies for pain and pain relief are central to experimental models of placebo analgesia and nocebo hyperalgesia and are a promising target for clinical intervention in patients with chronic pain. Affective states may play an important role in modulating the degree to which expectancies influence pain, broadening the opportunities for intervention targets. However, findings to date have been mixed and mostly limited to laboratory designs. Few studies have examined the interplay of naturally occurring affective states, pain expectancies, and pain experiences in the course of daily life with chronic pain. In this study, patients with temporomandibular disorder reported their daily pain expectancies and affective states each morning and their daily pain experience each evening, over a 2-week period. Multilevel modeling analyses revealed the association of morning pain expectancies with subsequent pain experiences was moderated by morning positive affective state ( B = 0.04, SE = 0.02, t = 2.00, P = 0.046) such that the congruent assimilation of a low pain expectancy with a low pain experience was starkest when morning positive affect was higher than usual. Relatedly, higher morning positive affect predicted greater odds of experiencing a match between pain expectancies and pain experience when the expectation was for low, but not high, pain levels (odds ratio = 1.19, confidence interval: 1.01-1.41, P = 0.03). Negative affect, in contrast, did not significantly influence the assimilation of high pain expectancies with high pain experiences. These findings extend previous experimental studies by showing that the association of daily pain expectancies with pain experience varies as a function of affective state.